Nieudany eksperyment socjalistycznej integracji. Rada Wzajemnej Pomocy Gospodarczej w latach 1949-1991 = A failed Experiment of Social Integration. Council for Mutual Economic Assistance in the years 1949-1991 - Skobelski, Robert (1968- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
RWPG (translator`s note: the Polish abbreviation of the Council for Mutual EconomicAssistance; the English abbreviation: COMECON) was founded on January 8th, 1949 at the will ofJoseph Stalin and was an important element in strengthening domination of the Union of SovietSocialist Republics in Central and Eastern Europe. In the beginning, the organization was supposedfirst of all to solidify and support the Russian economic model in the subordinate countries thatwas based on rejecting market principles and on focusing on central planning and extensiveindustrialisation.
Keywords: RWPG (Rada Wzajemnej Pomocy Gospodarczej); centralne planowanie; gospodarka; integracja; autarkia; COMECON (Council for Mutual Economic Assistance); central planning; economy; integration; autarky